A novel methodology providing insights into removal of biofilm‐mimicking hydrogel from lateral morphological features of the root canal during irrigation procedures. (3rd February 2014) - Macedo, R. G.; Robinson, J. P.; Verhaagen, B.; Walmsley, A. D.; Versluis, M.; Cooper, P. R.; van der Sluis, L. W. M.
Abstract Aim To introduce and characterize a reproducible hydrogel as a suitable biofilm mimic in endodontic research. To monitor and visualize the removal of hydrogel from a simulated lateral canal and isthmus for the following: I) Ultrasonic‐Activated Irrigation (UAI) with water, ii) UAI with NaOCl and iii) NaOCl without UAI. Methodology A rheometer was used to characterize the viscoelastic properties and cohesive strength of the hydrogel for suitability as a biofilm mimic. The removal rate of the hydrogel from a simulated lateral canal or isthmus was measured by high‐speed imaging operating at frame rates from 50 to 30 000 fps. Results The hydrogel demonstrated viscoelastic behaviour with mechanical properties comparable to real biofilms. UAI enhanced the cleaning effect of NaOCl in isthmi (P < 0.001) and both NaOCl and water in lateral canals (P < 0.001). A greater depth of cleaning was achieved from an isthmus (P = 0.009) than from a lateral canal with UAI and also at a faster rate for the first 20 s. NaOCl without UAI resulted in a greater depth of hydrogel removal from a lateral canal than an isthmus (P < 0.001). The effect of UAI was reduced when stable bubbles were formed and trapped in the lateral canal. Different removal characteristics were observed in the isthmus and the lateral canal, with initial highly unstable behaviour followed by slower viscous removal inside the isthmus. Conclusions The biofilm‐mimicking hydrogel is reproducible, homogenous and can be easily applied and modified. Visualization of its removal from lateral canal anatomy provides insights into the cleaning mechanisms of UAI for a biofilm‐like material. Initial results showed that UAI improves hydrogel removal from the accessory canal anatomy, but the creation of stable bubbles on the hydrogel–liquid interface may reduce the cleaning rate.